Medical waste disposal at BRAC Health Centres : an environmental study - Akter, Nasima; Acott, Rachael E; Sattar, M G; Chowdhury, Sadia A (BRAC Research and Evaluation Division (RED), 2020)
The study was conducted to determine the awareness level of BRAC's Health Centre staff on disposal and handling of medical wastes, and to recommend improved methods to handle and dispose of medical waste in order to minimize the adverse impact on human health and the environment. Data was collected from 14 BHCs between during December to March 1997 from Mymensingh and Dinajpur districts using a two pronged approach: (i) field observations, and (ii) interviews. It was found that the health centers that dealt with deliveries and laboratory facilities produce hazardous and pathological waste. There ts insufficient awareness of the magnitude of the medical waste issue by health care workers and their beneficiaries Proper laboratory techniques (both preparation and analysis), and disposal of waste water are overlooked. In BHCs waste was burnt in open pits behind the clinic facilities and buried in the ground, and there was rarely a fixed location. The chemicals used for the staining and preservation of slides for the sterilization and cleaning of equipment and surroundings are potentially harmful to the laboratory technician and the environment. There has been no formal training of staff to teach them how to deal with the disposal of medical wastes, although they received training on laboratory analysis, but it is done on an adhoc basis. Environmental and health impacts associated with laboratory, delivery and tuberculosis wastes are: accumulation of toxic chemicals within the soil (proximity to agricultural fields. humans. soil organisms, wildlife, cattle); ground water contamination; public nuisance; improper sterilization of instruments used in labour room causing infection to mother and child; habitat destruction due to the increasing the number of sites necessary for disposal of degradable and non-degradable wastes. Open air burning does not guarantee proper incineration, and releases toxic fumes into the atmosphere from the burning of plastics i.e., PCB's. In conclusion. it can be said that close monitoring of existing safety regulations and guidelines. increasing awareness on environmental hazards, and proper waste management planning m needed to ensure health and environmental safety.